Economic War: Ukraine and the Global Conflict between Russia and the West by Maximilian Hess (The Pakistan Development Review, 2025)
“Economic War: Ukraine and the Global Conflict between Russia and the West” by Maximilian Hess is not only a historical account of a conflict between Russia and the West but a critical analysis of the economic power struggles between the two. The book explicitly highlights the political problem that emerged when Russian President Vladimir Putin hit Ukraine in 2014 and the economic warfare that followed the event. Hess explores Russian strategies behind the scenes and against the sanctions, focused on pursuing global power. The author’s extensive research and deep analytical skills make the book an essential part of the knowledge impartation related to the intricate economic problems found within the conflict between Russia and the West on an international scale.Maximilian Hess is a political risk analyst, consultant, and research fellow at the Foreign Policy Research Institute. Hess possessed notable strengths in the areas of trade, debts, diplomacy, and foreign policy. These strengths allowed him to become an accomplished writer who could effectively discuss the economic problems that affected Russia and the West. He has authored numerous articles on Russia and its neighbouring countries, which eventually led to the publication of his first book in partnership with Hurst and Oxford University Press in 2023.In “Economic War: Ukraine and the Global Conflict between Russia and the West,” the author asserts that the present confrontation between Russia and the West is not the new Cold War but a struggle to influence the spheres of finance, energy, and capital markets. Economic war is defined as “the use of economic means to achieve geopolitical objectives or the use of geopolitical objectives to achieve economic ends.” Hess merges history with an analysis of the economic war, which has a long-term effect on liberalism, democracy, and the structure of the world’s economy. The author gives a clear and profound description of how the West preferred to use international markets to inflict pain on the Kremlin, and the Russian reaction was to seek the involvement of countries like China, Turkey, and Iran in the process.